Risk factors and outcomes associated with true knots of the umbilical cord: A retrospective study - Shouzhen Chen; Zhaozhen Liu; Qian Lin; Liping Huang (Taiwanese Journal of Obstetrics & Gynecology)
Objective: To investigate the pregnancy outcomes and independent risk factors associated with true knots of the umbilical cord (TKUC). Materials and methods: This retrospective study included 8140 deliveries at Fujian Maternal and Child Health Hospital from 2017 to 2021. Mothers and newborns diagnosed with TKUC were included in the TKUC group, while the others were included in the control group. The data were obtained from the hospital's electronic medical record system. Multiple pregnancies were excluded. Results: The incidence of TKUC was 0.61 %. The TKUC group had significantly higher proportions of advanced maternal age, multiparae and mothers with more than two pregnancies (P < 0.05). The neonates in the TKUC group were more male, had longer lengths and umbilical cords, heavier placentas, and a higher incidence of umbilical cord entanglement (P < 0.05). In terms of pregnancy outcomes, the TKUC group exhibited higher rates of cesarean section and preterm birth (P < 0.001; P < 0.05). However, there were no significant differences in birthweight, Apgar scores, stillbirth rate, and neonatal malformation rate between the two groups (P > 0.05). The results of logistic regression indicated that multiparae (OR = 1.386, P = 0.001), male fetus (OR = 1.499, P < 0.001), excessive long umbilical cord (OR = 11.022, P < 0.001), and umbilical cord entanglement (OR = 1.284, P = 0.019) were risk factors for TKUC. Conclusion: Male fetus, multiparae, umbilical cord entanglement, and especially excessively long umbilical cord were identified as independent risk factors for TKUC. TKUC had a minimal impact on the newborn's condition at birth, while it's associated with higher rates of cesarean section and preterm birth.